KESIAPAN SEKOLAH MENGHADAPI OSN EKONOMI SMA DI KOTA PADANG - Menik Kurnia Siwi; Nayang Helmayunita; Vanica Serly (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
The purpose of this research is to know the readiness of school in facing high school economic olympics in Padang. The method used in this activity is survey method to teacher of MGMP Economic Senior High School Padang, West Sumatera Province. The results of the study indicate that students are in need of coaching from teachers on Olympic materials and discussion of economic Olympic issues. Students are still in enough category (70.37%) mastering the economic Olympiad material. For that, teachers is expected to foster students to be more ready to follow the economic Olympics. Furthermore, schools need to hold special coaching of students with economic achievement by forming clubs or others so that students are more focused in understanding the OSN related material.